Prevalence of non A to E hepatitis in Mumbai, India - Nagral, Nishtha (2018)
Introduction: Acute viral hepatitis is a common problem in India. World wide data shows that 5 to 20 percent of this iscaused by non A-E hepatitis. There is no data in India regarding non A-E hepatitis. We carried out this study to evaluate theepidemiology, clinical features, risk factors and outcome of non A-E hepatitis. Material and methods: In this single centrestudy, we evaluated all patients admitted with features of acute viral hepatitis at our hospital between the period of Februaryto July 2015. A detailed history about the epidemiology, risk factors and clinical features was done. Patients were evaluatedwith bilirubin, transaminases and prothrombin time. Each patient was investigated for IgM HAV, IgM HEV, HBsAg and Antibodyagainst hepatitis C. Patients turning out negative were investigated for presence of autoimmune hepatitis or Wilson’s disease.All viral markers were repeated a week later to confirm non A-E status. Results: A total 265 patients were included of which41 (15.4%) patients were non A-E hepatitis. They had higher age (28.55 vs 34.99, p<0.05) but similar gender and sub urbanlocation. Median SEC classification was A2 in hepatitis A/E group as compared to A3 in non A-E group. The duration ofsymptoms and clinical features between the two groups were similar with Anorexia, Malasie, Nausea/vomiting being mostcommon. The risk factors between the two groups were similar. The bilirubin and transaminases were non significantly lowerthan hepatitis A/E patients while albumin levels were significantly lower. The outcomes of both groups were similar with nomortality or fulminant hepatitis. Conclusion: Non A-E hepatitis patients tends to be older, lower SEC class and had loweralbumin levels as compared to hepatitis A/E.